EFEKTIVITAS PENGGUNAAN MEDIA PUZZLE UNTUK MENINGKATKAN BERPIKIR KRITIS PESERTA DIDIK DI SEKOLAH DASAR - Mustasphia, Anggi Niswa; Sunaengsih, Cucun; Yusuf Ali, Enjang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of puzzle media in improving the critical thinking skills of fifth-grade students in social studies at Wado Elementary School. The background of this study is the low critical thinking skills in the social studies learning process. This study used a quasi-experimental method with a Nonequivalent Control Group Design. The subjects in this study were fifth-grade students consisting of 32 students from the experimental class and 30 students from the control class. Data collection techniques were carried out through tests (pretest and posttest). The results showed that there was a significant increase in posttest scores in the experimental class with an average of 71.29, which is included in the fairly effective category, while the control class only reached 31.43, which is included in the ineffective category. Based on these results, it can be concluded that puzzle media is effective in improving students' critical thinking skills in social studies learning in elementary schools.